Liberating the Repressed Self among Contemporary Chinese : A Theoretical Study Involving Tu Weiming and Jürgen Moltmann - Hwang, Tsung-I, (Beiträge zur Komparativen Theologie ;, 2025)
Blessed are those who are free to open their heart and unveil their hidden true selves. For their relational selfhood are graciously morally-cultivated in the community of grace. The repressed form of self (RFS) that is caused by relational selfhood under repressive social impositions is prevalent in contemporary Ru-influenced Chinese (CRIC) societies. For it is a significant factor causing a variety of emotional, psychological, interpersonal and communicative problems, and even suicide. This study first examines Tu Weiming's New Ruist relational selfhood and demonstrates that the features of Tu's account are not significantly different from the features of CRIC relational selfhood. Subsequently, the study examines Jürgen Moltmann's Christian social trinitarian relational selfhood, featuring an open relational self, embedded within a dynamic diversity in unity as well as a unity in diversity. Hwang argues that Moltmann's account contains a positive potentiality to liberate the RFS.